The Implementation of Project Based Learning (PjBL) in Improving Financial Literacy of Grade 5 Students through Financial Education Materials in Elementar Schools - Nurhaliza, Astria Tristiana (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
Financial Literacy Education is something that has not been well developed, both within the family, school, and community. Providing education about financial literacy is still not done seriously and planned. Financial Literacy Education is needed to educate people who are aware and understand how to manage finances wisely and according to their needs. Financial education is very important for all ages, especially children. Education on how to manage finances wisely according to needs. This qualitative research aims to explore the implementation of Project-Based Learning (PjBL) as an approach to improve students' financial literacy in elementary school through financial education materials. Through in-depth interviews, classroom observations, and project document analysis. This research aims to deeply understand the impact of PjBL on students' understanding of financial concepts and money management skills. The findings of this qualitative research are expected to provide valuable contextual insights in developing more effective financial education strategies at the primary level.